2012
DOI: 10.1105/tpc.112.102475
|View full text |Cite
|
Sign up to set email alerts
|

Lysin Motif–Containing Proteins LYP4 and LYP6 Play Dual Roles in Peptidoglycan and Chitin Perception in Rice Innate Immunity

Abstract: Plant innate immunity relies on successful detection of microbe-associated molecular patterns (MAMPs) of invading microbes via pattern recognition receptors (PRRs) at the plant cell surface. Here, we report two homologous rice (Oryza sativa) lysin motif-containing proteins, LYP4 and LYP6, as dual functional PRRs sensing bacterial peptidoglycan (PGN) and fungal chitin. Live cell imaging and microsomal fractionation consistently revealed the plasma membrane localization of these proteins in rice cells. Transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
267
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(279 citation statements)
references
References 47 publications
(85 reference statements)
5
267
2
5
Order By: Relevance
“…Given the plethora of small, defense-associated molecules involved in plant defense, it must be determined which of these have a role in intercellular signaling. With respect to the different mechanisms of chitin perception between rice and Arabidopsis, it remains to investigate chitin-triggered PD closure in rice and whether this is mediated by the CEBiP/OsCERK1 complex or by another member of the lysin motif-containing protein family (27). The purpose served by a reduction in cellto-cell communication during defense responses remains to be explained, but through its identification and its protein mediator, we can now actively pursue deeper questions relating to PD function during plant-pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Given the plethora of small, defense-associated molecules involved in plant defense, it must be determined which of these have a role in intercellular signaling. With respect to the different mechanisms of chitin perception between rice and Arabidopsis, it remains to investigate chitin-triggered PD closure in rice and whether this is mediated by the CEBiP/OsCERK1 complex or by another member of the lysin motif-containing protein family (27). The purpose served by a reduction in cellto-cell communication during defense responses remains to be explained, but through its identification and its protein mediator, we can now actively pursue deeper questions relating to PD function during plant-pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our former data, in which knockdown of either OsLYP genes could increase rice susceptibility to both fungal and bacterial pathogens. 10 Considering that these microbial pathogens contain a cocktail of MAMPs, 11 these data suggested that PGN or chitin signaling mediated by OsLYP4 and OsLYP6 contributes significantly to rice defense responses against bacteria and fungi.…”
Section: Oslyp4 and Oslyp6 Affected Pathogen-induced Defense-related mentioning
confidence: 99%
“…10 Moreover, another lysin motif-containing protein, CEBiP has been reported to play important role in chitin sensing and signal transduction. 12,13 Therefore, we investigated the protein-protein interactions between these LYP proteins with yeast two-hybrid (Y2H).…”
Section: Oslyp4 and Oslyp6 May Cooperate With Other Lysm-containing Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant cell surface-localized immune receptors, also called pattern-recognition receptors (PRRs), consist of a variety of receptor-like kinases and receptor-like proteins. Many PRRs, including FLS2, EFR, Xa21, CERK1, CEBiP, LYM1, LYM3, LYP4, and LYP6 (1)(2)(3)(4)(5)(6)(7)(8), directly sense pathogen/microbe-associated molecular patterns (PAMPs), such as flagellin, elongation factor, quorum-sensing protein, or peptidoglycans from bacteria or chitin from fungal cell wall. In addition to PAMPs, PRRs also perceive endogenous damage-associated molecular patterns (DAMPs), such as plant cell wall fragments released by pathogen lytic enzymes or plant peptides synthesized de novo during pathogen infection.…”
mentioning
confidence: 99%